EDUCATIONAL VALUES IN ROMANS: LE ROUGE ET LE NOIR/THE RED AND THE BLACK AND THE CHARTREUSE OF PARMA WRITTEN BY STENDHAL - Nuryadin, Sulandri (IJLECR (International Journal of Language Education and Cultural Review), 2017)
This scientific work is a qualitative research content analysis with genetic structural approach. The objective of this research to meet the existing educational values ​​in the novels The Red and the Black and The Charterhouse of Parma. This research began in November 2013 in Jakarta. Data for this research were taken of the novels to discuss as well as books about the life of the writer and French history in the nineteenth century. The analysis is based on the genetic and structural approach on historical data. The results of this research show that there are educational values ​​explicitly and implicitly in novels studied related to social events that took place at the time the novels were written. They appear in the learning-teaching, religion, social and political events. These values ​​can play a relevant role that can influence the behavior of readers. They could be people who put worth reading will; the desire to.acquire languages a..language like..Latin..andcuriosity..towards a colosal..event. The results of this research could motivate university students of French to find the pleasure of reading novels in order to enrich them selves intellectually and culturally.